Akal dan Otak dalam Telaah Al Qur'an dan Neurosains - Khotimah, Ihda Husnul; Suyadi, Suyadi (MASALIQ, 2023)
Theoretical conflict in the study of the Qur'an and neuroscience related to reason and the human brain is the main problem underlying this research. Specifically, the meaning of the brain has not been stated in the Qur'an. Universally, reason plays a role as a thinking potential in humans. However, the mind and the brain are an inseparable unit. Although the form of reason itself is formless, there is a brain as a storage container. Humans are God's most perfect creatures because of their reason. In addition, humans were also created by God in the best form. This study aims to examine more deeply the concept of reason and the human brain from the perspective of the Qur'an and Neuroscience. The method used in this study is descriptive qualitative with data sources obtained through literature study with various references. The results of the research show that the concepts of mind and brain are interconnected entities. By utilizing both of them properly, humans will be able to become caliphs on the face of God's earth. Humans should make use of their minds and brains in accordance with their functions and in line with religious law and optimize all their potential which is centered on reason and brain. The results of the research can add to the body of knowledge and have special implications for educators, both lecturers at school and parents within the family, to always optimize the function of the mind and brain.